Internal Impingement of the Shoulder: A Risk of False Positive Test Outcomes in External Impingement Tests?. (20th August 2017) - Leschinger, Tim; Wallraff, Christopher; Müller, Dirk; Hackenbroch, Matthias; Bovenschulte, Henning; Siewe, Jan
Abstract : Background . External impingement tests are considered as being particularly reliable for identifying subacromial and coracoid shoulder impingement mechanisms. The purpose of the present study was to evaluate if these tests are likely to provoke an internal shoulder impingement mechanism which, in cases of a pathologic condition, can lead to a positive test result. Method . In 37 subjects, the mechanical contact between the glenoid rim and the rotator cuff (RC) was measured quantitatively and qualitatively in external impingement test positions using an open MRI system. Results . Mechanical contact of the supraspinatus with the posterosuperior glenoid was present in 30 subjects in the Neer test. In the Hawkins test, the subscapularis was in contact with the anterosuperior glenoid in 33 subjects and the supraspinatus in 18. In the horizontal impingement test, anterosuperior contact of the supraspinatus with the glenoid was identified in 35 subjects. Conclusion . The Neer, Hawkins, and horizontal impingement tests are likely to provoke the mechanism of an internal shoulder impingement. A posterosuperior internal impingement mechanism is being provoked predominately in the Neer test. The Hawkins test narrows the distance between the insertions of the subscapularis and supraspinatus and the anterosuperior labrum, which leads to an anterosuperior impingement mechanism.